Case report: Rare presentation of double primary malignancies of the lung and thyroid: a difficult diagnosis - Chen, Shun-Ping; Li, Peng; Pan, Yi-Fei; Jiang, Xin (Frontiers in Oncology, 2024)
This report describes a rare case of double primary cancer in a female patient aged 49 years who died 2 years after diagnosis. The patient was diagnosed with BRAFV600E-mutant metastatic papillary thyroid carcinoma (PTC) and ALK fusion-positive metastatic lung adenocarcinoma. She presented with multifocal thyroid lesions and underwent radical thyroidectomy and bilateral cervical lymphadenectomy. Thyroid ultrasound revealed the presence of five hypoechoic nodules with irregular margins and microcalcifications; an irregular inhomogeneous hypoechoic level IV cervical lymph node was also found on the right side. Histological analysis confirmed the presence of metastatic PTC, and the tumor tested positive for the BRAFV600E mutation. Ultrasound of the neck, which was performed 4 months postdischarge, revealed enlargement of the left-sided cervical lymph nodes; a biopsy from these nodes confirmed a diagnosis of metastatic PTC. Positron emission tomography-computed tomography scans revealed the presence of multiple pulmonary hypermetabolic foci scattered across bilateral lung fields. Multiple hypermetabolic foci were also observed in the lymph nodes on both sides of the neck, axillae, and mediastinum; in addition, there was evidence of bone destruction with hypermetabolic foci. Supplementary reports from the histological and immunohistochemical analyses of cervical lymph node tissue obtained during primary surgery confirmed the presence of metastatic PTC and poorly differentiated lung adenocarcinoma. In particular, one enlarged cervical lymph node located on the right side of the neck demonstrated tumor components of both PTC and lung adenocarcinoma. Pathological analysis of axillary lymph node puncture biopsy confirmed the presence of metastatic lung adenocarcinoma, and gene analysis revealed the presence of ALK fusion. The patient received targeted therapy based on a multidisciplinary discussion. However, she had a poor prognosis and died 2 years after the diagnosis. The initial thyroid ultrasound findings were reviewed retrospectively; the findings suggested that the possibility of double primary cancers should be considered in cases where the enlarged cervical lymph nodes are highly suspicious of PTC and present as inhomogeneous hypoechoic masses with irregular morphology.